Thermal effect on unsteady flow of a dusty visco-elastic fluid between two parallel plates under different pressure gradients - R, Madhura K.; G, Kalpana (International Journal of Engineering and Technology, 2013)
This article describes the effect of thermal diffusion on a flow of dusty viscous incompressible fluid which is electrically conducting and the flow is between two vertically heated, porous, parallel plates with heat source or sink. Variable separable and Laplace transform techniques are used to attain the solution of the mathematical equations. The effect of the temperature is examined for different values of Prandtl number (Pr). The consequences of the concentration is observed for different values of thermal diffusion parameter (Td). The velocity profile for the flow of fluid and the dust particles are discussed for different values of Td and chemical reaction parameter (cr). In addition to that, the solutions are exhibited graphically.